Informal learning, organizational commitment and self-efficacy: A study of a structural equation model exploring mediation. Issue 8 (15th November 2018) - Yoon, Dong-Yeol; Han, Seung-hyun; Sung, Moonju; Cho, Jun
Abstract : Purpose: This paper aims to explore a mediating effect of self-efficacy between individuals' informal learning and their organizational commitment. Informal learning between individuals is critical in the workplace because sharing knowledge and expertise is directly related to employee's attitude and organizational benefits such as enhanced performance and productivity. Of the many factors affecting organizational commitment, this research focuses on effects of informal learning and a mediating role of self-efficacy. Design/methodology/approach: To address these research questions, this research analyzes survey data of 317 Korean workers. Through structural equation model analysis, the authors examine how informal learning affects employee commitment to organizations, where individual self-efficacy works as a mediator. Findings: The analysis confirms that informal learning increases self-efficacy, whereas no directly influences organizational commitment. The analysis also demonstrates that self-efficacy mediates the relationship between informal learning and organizational commitment. This study confirms the positive relationship between informal learning and self-efficacy, whereas no direct relationship between informal learning and organizational commitment. Research limitations/implications: This study has several limitations in terms of methodology. Data collection mainly relied on a survey method, which is a single source and raises the concern of common method bias. Therefore, future studies may use different types of data to solve the problem of common method biases. In addition, the study design was cross-sectional; therefore, it was unable to eliminate the biases caused by simultaneous data. Future studies can adopt a longitudinal design using different time stages to collect data in order to eliminate this bias. Originality/value: The main reasons for the high rate of informal learning through activities such as on-the-job training, coaching, mentoring and community of practice include the increase in the efficiency of learning and reduction in learning costs by integrating learning and work and the effectiveness of informal learning in terms of improving performance. This research seeks to demonstrate how informal learning in the workplace influences employees' commitment to the organization through self-efficacy.